Integration of Visual Branding and User Experience in the Design of the Nusantara Rempah Marketplace Application - Rossyta Wahyutiar; Alexander Wirapraja; Jocelyn Leslie Santoso Go (Universitas Islam Raden Rahmat, Malang, 2026)
Indonesia has significant potential as one of the world's leading spice producers; however, digital platforms that integrate spice marketing and education remain limited. This study aims to design Rempahara, a spice marketplace application that integrates visual branding and user experience to improve digital transactions while providing educational content on Indonesian spices. The study employed the Design Thinking method, consisting of the Empathize, Define, Ideate, Prototype, and Test stages. A high-fidelity prototype was evaluated through usability testing involving 30 respondents selected using purposive sampling, comprising users familiar with marketplace applications and interested in cooking or spice products. The evaluation used Task Success Rate, Error Rate, and Time on Task metrics. The results showed a Task Success Rate of 97.1%, an Error Rate of 2.9%, and an Average Completion Time of 26.6 seconds. According to usability effectiveness criteria proposed by ISO 9241-11 and Nielsen's usability principles, these results indicate that the application demonstrates high usability, enabling users to complete tasks effectively and efficiently. Therefore, integrating visual branding and user experience can provide an intuitive and informative digital marketplace for Indonesian spices.